CBARA1 plays a role in stemness and proliferation of human embryonic stem cells. - Kevin Chen; Lih-Tao Hsu; Cheng-Yi Wu; Shiun-Yin Chang; Hui-Ting Huang; Wannhsin Chen (PLoS ONE, 2013)
Human embryonic stem cells (hESCs) are capable of unlimited self-renewal and can generate almost all of the cells in the body. Although some pluripotency factors have been identified, much remains unclear regarding the molecules and mechanisms that regulate hESC self-renewal and pluripotency. In this study, we identified a mitochondrial gene, CBARA1, that is expressed in undifferentiated hESCs and that is down-regulated rapidly after cellular differentiation. To study its role in hESCs, endogenous CBARA1 expression was knocked down using shRNA. CBARA1 knockdown in hESCs resulted in down-regulation of Oct4 and Nanog expression, attenuated cell growth, and G0/G1 phase cell cycle arrest; however, knockdown did not noticeably affect apoptosis. Taken together, these results suggest that CBARA1 is a marker for undifferentiated hESCs that plays a role in maintaining stemness, cell cycle progression, and proliferation.